A Strategic Planning Methodology for the Multimodal Transportation Systems: A Case Study from Turkey - Tuzkaya, Umut R.; Onut, Semih; Tuzkaya, Gulfem (HINDAWI PUBLISHING CORPORATION, 2014)
Transportation costs have an important effect on companies' competition capability in various sectors. To realize a positive effect, transportation industry should provide some specific performance criteria related with the economical efficiency and service quality. Also an increase in this performance degree depends on the obtaining optimum results of using the logistical resources in a convenient manner by the specialized logistics service providers. In this study, considering the effects of transportation modes on constituting a methodology that is interested in a strategic subject like constructing a transportation network is emphasized. In the process of selecting the most convenient transportation modes, all the required criteria are determined considering the related literature and the opinions of the experts. Then the analytical network process methodology is used to solve this selection problem. The close relationship between the transportation modes that will be used among the points in the network and the points that will be used for short storages and transshipment activities is considered. And the analytical network process is again used to select the most convenient ones among the alternative port locations. After decision making on these two important points, optimizing the freight flow among the supply chain by choosing the right transportation modes at each stage is aimed. To realize that optimization, the aims of decision makers from different levels or from different functional areas are satisfied by using the multilevel programming technique. Finally, the proposed methodology is applied on a transportation project of a logistic service provider, which gives service in a multimodal, multicommodity, multilevel and multiechelon transportation network.
Keywords: MULTIOBJECTIVE DECISION-MAKING; SUPPLY CHAIN; PROGRAMMING-PROBLEMS; FUZZY; OPTIMIZATION; ALGORITHM; SELECTION; NETWORKS; Mathematics